A game theory application in the copper market. (March 2021) - Otgochuluu, Ch.; Altangerel, L.; Battur, G.; Khashchuluun, Ch.; Dorjsundui, G.
Abstract: Mongolia has a small open economy that is growing due to its status as one of the major copper exporters in the Asian copper market. We used game theory to analyze the Chinese copper market and determine the competitive strategies used by Mongolian exporters. We show that a variational inequality approach is one option to prove that game theory is applicable in the analysis of the Chinese copper market, as it is spatial and concentrated. To solve the profit maximization problem with a concave objective function for each player and linear strategy set, it can be reduced to variational inequalities. Numerical calculations allow us to predict the responses of certain parameters against external factors or so-called non-economic shocks, such as changes in Chinese import policies, strikes in Chile, etc. In the future, if Mongolia builds a new copper smelter, it will be a competitor within a more concentrated market than that of the current copper concentrate trade. Thus, the importance of developing such a model is increasing.